Perbandingan Efektivitas Foot Massage dengan Head Massage Terhadap Penurunan Tekanan Darah pada Lansia dengan Hipertensi di Desa Sampali - Waruwu, Seni Warni; Sagala, Lam Murni; Hasibuan, Muhammad Taufik Daniel (Pustaka Galeri Mandiri, 2026)
Hypertension is blood pressure that experiences an increase in systolic more than 140 mmHg and diastolic more than 90 mmHg and is measured in two measurements within a period of five minutes, and the patient's condition is not tired. To determine the difference in the effectiveness of foot massage with head massage on reducing blood pressure in the elderly with hypertension in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency. Quantitative research method with quasi-experiment with a two group pretest and posttest group design approach and divided into 2 groups with different treatments. The sampling technique is purposive sampling and a sample of 52 people. data analysis used is univariate and bivariate with independent samples t test. The results of this study indicate that there is a difference in the effectiveness of foot massage with head massage on reducing blood pressure in elderly with hypertension, namely p value 0.001 <0.005 where the average value of the decrease in both groups was 146.65 / 97.35 mmHg in the foot massage group and 141.77 / 88.31 mmHg in the head massage group. It is concluded that head massage therapy has a greater decrease in blood pressure when compared to foot massage. for further research, it can continue research on nursing care for hypertensive patients and also as a reference in making further papers